2017
DOI: 10.1111/mec.14200
|View full text |Cite
|
Sign up to set email alerts
|

Increase in multiple paternity across the reproductive lifespan in a sperm‐storing, hermaphroditic freshwater snail

Abstract: Polyandry is a common phenomenon and challenges the traditional view of stronger sexual selection in males than in females. In simultaneous hermaphrodites, the physical proximity of both sex functions was long thought to preclude the operation of sexual selection. Laboratory studies suggest that multiple mating and polyandry in hermaphrodites may actually be common, but data from natural populations are sparse. We therefore estimated the rate of multiple paternity and its seasonal variability in the annual, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…In Lake Zurich, Switzerland, it exhibits an annual life cycle with non-overlapping generations. Snails hatch from eggs in spring, reach sexual maturity in winter, reproduce from March to May, and then die [ 55 ]. During the single breeding season, individuals may copulate repeatedly in both sexual roles and lay hundreds of eggs in distinct egg clutches [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Lake Zurich, Switzerland, it exhibits an annual life cycle with non-overlapping generations. Snails hatch from eggs in spring, reach sexual maturity in winter, reproduce from March to May, and then die [ 55 ]. During the single breeding season, individuals may copulate repeatedly in both sexual roles and lay hundreds of eggs in distinct egg clutches [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Morris et al (2006) showed that, across five species of perennial plants in the USA, vital rates including seedling survival (equivalent to 𝑆𝑆 𝐽𝐽 here), survival at other stages, growth, germination, and seed production (equivalent to 𝑓𝑓 here) showed nonlinear change as a function of time since last hurricane or fire disturbance (disturbance phase). Similarly, Bürkli & Jokela (2017) showed that embryonic development success (early-stage juvenile survival) 13 of a freshwater snail changed nonlinearly across the species' reproductive season. The exact shape of vital rate response functions is another key point to be tailored for system-specific inquiry, whether with empirical measurements or as realistic assumptions built into models.…”
Section: A Simple Demographic Model In Fluctuating Environmentsmentioning
confidence: 99%
“…In Lake Zurich, Switzerland, it is an annual with non-overlapping generations. Snails hatch from eggs in spring, reach sexual maturity in winter, reproduce from March to May, and then die (48). During the single breeding season, individuals may copulate repeatedly in both sexual roles and lay hundreds of eggs in distinct egg clutches (48).…”
Section: Study Systemmentioning
confidence: 99%
“…Mating trials began in early May 2014 when F1 snails were 52.1 ± 1.0 weeks old and 38.7% had selfed in isolation. In the ancestral field population, breeding started in early March (48), and laboratory control snails had started to copulate several weeks earlier (see above). The experiment then continued for seven weeks, until mortality began to increase reflecting the snails' natural, annual life cycle.…”
Section: Mating Trialsmentioning
confidence: 99%
See 1 more Smart Citation